Application of laser ultrasonic technique for non-contact detection of structural surface-breaking cracks. (October 2015) - Zhou, Zhenggan; Zhang, Kuanshuang; Zhou, Jianghua; Sun, Guangkai; Wang, Jie
Abstract: Based on the finite element method (FEM), the surface-breaking cracks have been investigated by using the laser-generated Rayleigh wave. The features of laser-generated Rayleigh wave interaction with cracks are analyzed in time and frequency domain. The simulation results show that the surface acoustic wave induced by the pulsed laser is sensitive to the surface-breaking cracks. As the crack depth increases, the transmission coefficients almost linearly decrease and the reflection coefficients show a dip. The corresponding experimental results have verified the feasibility of numerical calculation and reached a good agreement with simulation results. The research findings would provide a potential application for testing surface-breaking cracks of aircraft parts. Highlights: We research the interaction of laser-generated Rayleigh wave with cracks. Increasing crack depth will decrease transmission coefficients of Rayleigh wave. Reflection coefficients of Rayleigh wave show a dip as crack depth increases. We investigate the quantitative characterization of surface-breaking cracks.